Expression profiles of microRNA-mRNA and their potential impact on anthocyanin accumulation in purple petals of Brassica napus - Chen Tan; Qi Zhang; Wenjie Shen; Yi Liu; Dawei Zhang; Lunlin Chen; Daozong Chen (BMC Plant Biology)
Abstract Rapeseed (Brassica napus L.) possesses substantial economic value as an oil, vegetable, and forage crop, while also exhibiting notable ornamental characteristics. Recent advances in flower colour breeding have significantly enhanced the visual appeal of rapeseed, with anthocyanins identified as the primary contributor to the development of red, purple, and pink flowers. However, the mechanisms underlying the synthesis and regulation of anthocyanins during petal coloration in rapeseed are still poorly understood. This research combined miRNA and mRNA expression data from four different color phases, along with degradome analysis, to discover important miRNA-mRNA modules responsible for controlling the accumulation of anthocyanin in purple-flowered rapeseed. In the process of petal development, a grand sum of 247 miRNAs (including 223 known and 24 novel miRNAs) were effectively detected, with 64 of them displaying differential expression patterns. Degradome sequencing was used to conduct a comprehensive analysis of 152 targets for the differential expression miRNAs. Out of these, 108 miRNA-mRNA modules exhibit contrasting expression patterns. Some miRNAs and their corresponding targets have additionally been discovered, potentially playing a role in governing the buildup of anthocyanin in purple-flowered rapeseed. The regulatory modules miR156-SPL9 and miR828-PAP2 composed of miR156b and miR828 and their targets may play a key role in this process. The results offer a thorough analysis of miRNAs linked to the regulation of anthocyanin in B. napus, offering valuable understanding into the regulatory processes that govern miRNA-mediated anthocyanin production in Brassica crops.